IMPLEMENTASI FISHER YATES SHUFFLE UNTUK MENGACAK OBJEK PADA PEMBELAJARAN VOCABULARI SISWA SD MENGGUNAKAN CONSTRUCT 2 - Liswintiawati, Ida; Ardhianto, Eka (Information Technology and Telematics, 2018)
ABSTRACT Along with the rapid development of this technology can not be denied that foreign language, especially English is very important. However, not a few students whose English learning achievement is adequate. especially with the method of learning is still manual while the development of technology now the kids are more interested in smartphone games, the impact of the English language values ​​of these children are not in accordance with the existing KKM. Therefore the author wants to make game "vocabulary learning" which is expected to be able to help elementary students meet the value of KKM and can reproduce about vocabulary. In making this educational game the author uses the Fisher Yates Shuffle method. This game there are three learning vocabulary namely: the name of the animal, the name of the fruit and the name of the object, in which there are images of objects and sound pronunciation in English. The results showed that educational games "Vocabulary Learning" created using Construct 2 can be run on mobile devices android platform easily by the user.Keywords: Game, Construct 2, android, Learning, Vocabulary